Multihelix rotating shield brachytherapy for cervical cancer. Issue 11 (20th October 2015) - Dadkhah, Hossein; Kim, Yusung; Wu, Xiaodong; Flynn, Ryan T.
Abstract : Purpose: To present a novel brachytherapy technique, called multihelix rotating shield brachytherapy (H‐RSBT), for the precise angular and linear positioning of a partial shield in a curved applicator. H‐RSBT mechanically enables the dose delivery using only linear translational motion of the radiation source/shield combination. The previously proposed approach of serial rotating shield brachytherapy (S‐RSBT), in which the partial shield is rotated to several angular positions at each source dwell position [W. Yang et al., "Rotating‐shield brachytherapy for cervical cancer, " Phys. Med. Biol. 58, 3931–3941 (2013)], is mechanically challenging to implement in a curved applicator, and H‐RSBT is proposed as a feasible solution. Methods: A Henschke‐type applicator, designed for an electronic brachytherapy source (Xoft Axxent™) and a 0.5 mm thick tungsten partial shield with 180° or 45° azimuthal emission angles and 116° asymmetric zenith angle, is proposed. The interior wall of the applicator contains six evenly spaced helical keyways that rigidly define the emission direction of the partial radiation shield as a function of depth in the applicator. The shield contains three uniformly distributed protruding keys on its exterior wall and is attached to the source such that it rotates freely, thus longitudinal translational motion of the source is transferred to rotational motion of the shield. S‐RSBT and H‐RSBT treatment plans with 180° and 45° azimuthal emission angles were generated for five cervical cancer patients with a diverse range of high‐risk target volume (HR‐CTV) shapes and applicator positions. For each patient, the total number of emission angles was held nearly constant for S‐RSBT and H‐RSBT by using dwell positions separated by 5 and 1.7 mm, respectively, and emission directions separated by 22.5° and 60°, respectively. Treatment delivery time and tumor coverage ( D 90 of HR‐CTV) were the two metrics used as the basis for evaluation and comparison. For all the generated treatment plans, the D 90 of the HR‐CTV in units of equivalent dose in 2 Gy fractions (EQD2) was escalated until the D 2cc (minimum dose to hottest 2 cm 3 ) tolerance of either the bladder (90 Gy3 ), rectum (75 Gy3 ), or sigmoid colon (75 Gy3 ) was reached. Results: Treatment time changed for H‐RSBT versus S‐RSBT by −7.62% to 1.17% with an average change of −2.8%, thus H‐RSBT treatments times tended to be shorter than for S‐RSBT. The HR‐CTV D 90 also changed by −2.7% to 2.38% with an average of −0.65%. Conclusions: H‐RSBT is a mechanically feasible delivery technique for use in the curved applicators needed for cervical cancer brachytherapy. S‐RSBT and H‐RSBT were clinically equivalent for all patients considered, with the H‐RSBT technique tending to require less time for delivery.